"Save Archaeology from the Technicians": Wheeler, World Heritage and Expert Failure at Mohenjodaro. Issue 1 (9th May 2019) - Meskell, Lynn
Abstract: Between the 1960s and 1980s, the United Nations Educational, Scientific and Cultural Organization (UNESCO) launched a number of international salvage campaigns at the behest of its member states, the most notable being the Nubian Monuments Campaign. Saving ancient monuments and discovering archaeological sites in Egypt and Sudan was viewed as a landmark in twentieth-century heritage conservation and international co-operation; it was never to be repeated again. Requests for assistance continued, yet the campaigns were configured as conservation missions rather than integrated field projects. In retrospect, this action delimited UNESCO's goals to bridge education, science, and culture and, ultimately, impacted the potential of cross-cultural dialogue and partnerships afforded by archaeological field research. This article focuses on UNESCO's International Campaign for the Safeguarding of Moenjodaro (1974–97) and traces the role of experts, both archaeological and hydrological, within UNESCO's mission. It uncovers the organization's handling of the monumental challenges and long-term effects of a multimillion-dollar salvage effort. In doing so, the article reveals the early role of prominent archaeologists Mortimer Wheeler and John Otis Brew, the ideological shift at UNESCO from archaeological research to monumentality and preservation, and the tensions that emerged as world heritage was reimagined.